Insulin Receptor Isoform Variations in Prostate Cancer Cells - Perks, Claire M.; Zielinska, H. A.; Wang, Jing; Jarrett, Caroline; Frankow, A.; Ladomery, Michael R.; Bahl, Amit; Rhodes, Anthony; Oxley, Jon; Holly, Jeff M. P. (Frontiers in Endocrinology, 2016)
Men who develop prostate cancer increasingly have one of the co-morbidities associated with a Western lifestyle that are characterised by hyperinsulinemia, hyperglycaemia and increased expression of insulin-like growth factors-I and –II. Each have been associated with poor prognosis and more aggressive cancers that exhibit increased metabolism and increased glucose uptake. The insulin receptor has two splice isoforms IR-A and IR-B: IR-A has a higher affinity for IGF-II comparable to that for insulin, whereas the IR-B isoform predominantly just binds to insulin. In this study we assessed alterations in the IR-A and IR-B isoform ratio and associated changes in cell proliferation and migration of prostate cancer cell lines following exposure to altered concentrations of glucose and treatment with IGF-II and insulin. We observed that where IR-B predominated insulin had a greater effect on migration than IGF-II and IGF-II was more effective when IR-A was the main isoform. With regards to proliferation IGF-II was more effective than insulin regardless of which isoform was dominant. We assessed the abundance of the IR isoforms both in vivo and in vitro and observed that the majority of the tissue samples and cell lines expressed more IR-A than IR-B. Alterations in the isoforms in response to changes in their hormonal milieu could have a profound impact on how malignant cells behave and play a role in promoting carcinogenesis. A greater understanding of the mechanisms underlying changes in alternative splicing of the IR may provide additional targets for future cancer therapies.